2006
DOI: 10.2353/ajpath.2006.060260
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Bone Marrow Fibroblast Growth Factor-2 in the Effect of Estradiol on Reendothelialization and Endothelial Progenitor Cell Mobilization

Abstract: 17␤-Estradiol (E 2 ) accelerates reendothelialization and increases the number of circulating endothelial progenitor cells (EPCs), but whether fibroblast growth factor-2 (FGF2) is involved in these processesEndothelium, uniquely positioned at the interface between the blood and the vessel wall, plays a crucial role in the physiology of circulation by performing multiple functions.1 It is involved in the regulation of coagulation, leukocyte adhesion in inflammation, transvascular flux of cells, liquids and solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
0
32
0
1
Order By: Relevance
“…Third, platelets are abundant in the deendothelialized area (9,26) and release factors that can directly (32) or indirectly (27) contribute to accelerate reendothelialization. Indeed, we previously reported that BM FGF-2 is absolutely required in the accelerative effect of E 2 in reendothelialization, whereas extra-BM FGF-2 is dispensable (15), suggesting that FGF-2 is a key mediator of the E 2 action at the level of the BM. The en face analysis by EFCM does not suggest that BM-derived cells contribute substantially as cobblestones of the regenerated endothelial pavement, at least not in the repair process in the models used in the present study, in which the injury is limited to 4 mm and reendothelialization is completed after 1 wk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, platelets are abundant in the deendothelialized area (9,26) and release factors that can directly (32) or indirectly (27) contribute to accelerate reendothelialization. Indeed, we previously reported that BM FGF-2 is absolutely required in the accelerative effect of E 2 in reendothelialization, whereas extra-BM FGF-2 is dispensable (15), suggesting that FGF-2 is a key mediator of the E 2 action at the level of the BM. The en face analysis by EFCM does not suggest that BM-derived cells contribute substantially as cobblestones of the regenerated endothelial pavement, at least not in the repair process in the models used in the present study, in which the injury is limited to 4 mm and reendothelialization is completed after 1 wk.…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas the number of GFP-positive cells in the Regen was about 4% and very abundant in the adventitia, no GFP-positive cells could be detected in the media (Ref. 15 and not shown).…”
Section: D and Dј)mentioning
confidence: 99%
See 2 more Smart Citations
“…15,28 However, most of these experiments showed a correlation between EPC increase and acceleration of reendothelialization rather than a causative relationship. 29 To further characterize the relationship between BM-derived cells and the regenerating endothelial cell monolayer, we grafted GFP-BM to wild-type mice and found that only a few GFP-positive cells (3% to 4% of intima cells) were present at the level of the regenerated endothelial cell monolayer, irrespective of the E2 treatment. Noteworthy, they were no longer detectable 30 days postinjury, indicating that these cells did not incorporate into the regenerated endothelium.…”
mentioning
confidence: 99%